AB0203 Prevalence of tuberculin skin test reaction positivity in a colombian cohort of rheumatoid arthritis patients on biologic therapy. (23rd January 2014) - Arredondo, A. M.; Escobar-Trujillo, A.; Londono, J.; Gonzalez-Malaver, F.; Bello-Gualtero, J.; Guzman-Vergara, C.; Mesa-Betancourt, A.; Valle-Oñate, R.; ,
Abstract : Background: Colombia is considered an intermediate tuberculosis (TB)-burden country, so initial and annual tuberculin skin test (TST) control is mandatory for all Rheumatoid Arthritis (RA) patients on biologic therapy, especially those on anti-TNF therapy. Objectives: The aim of this study was to determine the prevalence of TST positivity in a cohort or RA patients from a Colombian rheumatology center, and its relationship with disease activity, biologic and non biologic therapy. Methods: A descriptive, cross sectional study was performed. Records of patients from a rheumatology center were revised. All RA patients on biological therapy where included, data about TST results (performed by mantoux method), previous active or latent TB treatment, DAS28, present and past biologic therapy as well as present non biologic therapy for RA and comorbidities where included. Percentages and averages where performed. Chi square test for categorical variables and wilcoxon test for numerical and categorical associations were performed on STATA 4 software. Results: 107 established-RA patients where included, 79 women (73.83%) and 28 men (26.17%), with an average age of 57.2 years old (36-82 SD 11.25). Average disease duration 4.4 years (0, 3-14, 1 SD 3.39). Average DAS28 2.8 (1, 1-6, 3 SD 1.09). Most patients where on anti TNF therapy, 38 (35.5%) on adalimumab, 20 (18.6%) on etanercept, 9 (8.4%) on infliximab and 3 (2.8%) on certolizumab; followed by 20 patients on rituximab (18.6%), 9 on tocilizumab (8.4%) and 8 on abatacept (7.4%). 18 patients had positive TST (16.8%). From the positive TST patients, 88.8% (16) received treatment for latent tuberculosis, and one for active tuberculosis. In the group of positive TST, 9 (50%) patients where on anti TNF therapy (6 on adalimumab, 2 on etanercept and 1 on infliximab), and 9 with other therapies (6 on rituximab, 2 on tocilizumab and 1 on abatacept), from these non anti TNF patients, 5 (55%) used anti TNF therapy in the past. In regard of non biologic DMARDs, from the patients with positive TST, 12 (66.6%) used methotrexate and 6 (33.3%) used prednisolone, while in the group of negative TST, 45 (50.56%) used methotrexate and 27(30.33%) prednisolone. Bivariate analysis showed no correlation between TST positivity and any biological treatment, prednisolone or methotrexate use, disease duration or comorbidities. Conclusions: 16.8% patients had positive TST in this cohort of Colombian RA patients, similar as found in other Latin American studies (1 ). Most TST positive patients where on anti TNF therapy or had a history of use of this therapy with no statistical significance. There was no correlation between the use of MTX or PDN and an anergic TST, as found in other RA studies (2 ). There's a need for the use of other latent-TB screening tests in our country (3 ). Further studies are needed to evaluate the impact of biologic therapy in the incidence of latent TB on RA in Colombia and Latin America. References: Tamborenea MN. Rheumatol Int. 2010. Bélard E. Inflamm Bowel Dis. 2011. Chang B. Clin Rheumatol. 2011 Disclosure of Interest: None Declared